2019
DOI: 10.1111/1348-0421.12671
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of Leptospira johnsonii sp. nov., Leptospira ellinghausenii sp. nov. and Leptospira ryugenii sp. nov. isolated from soil and water in Japan

Abstract: In a previous study, 50 of 132 soil samples collected throughout Japan were found to be Leptospira‐positive. In the present study, three strains identified in the collected specimens, three, E8, E18 and YH101, were found to be divergent from previously described Leptospira species according to 16S ribosomal RNA gene sequence analysis. These three strains have a helical shape similar to that of typical Leptospira and were not re‐isolated from experimental mice inoculated with the cultured strains. Upon 16S ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Several studies regarding the isolation of Leptospira from environmental samples, such as soil and water, using STAFF have been reported . As a result, Leptospira were found to be ubiquitous in the environment, and more than 40 novel species isolated from soil and water collected from all over the world are proposed . In our previous study, 37.9% of soil collected from all over Japan were found to be culture‐positive when using STAFF selective medium .…”
Section: Culture‐positivity Rate Of Leptospira In Environmental Watermentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies regarding the isolation of Leptospira from environmental samples, such as soil and water, using STAFF have been reported . As a result, Leptospira were found to be ubiquitous in the environment, and more than 40 novel species isolated from soil and water collected from all over the world are proposed . In our previous study, 37.9% of soil collected from all over Japan were found to be culture‐positive when using STAFF selective medium .…”
Section: Culture‐positivity Rate Of Leptospira In Environmental Watermentioning
confidence: 95%
“…Vincent et al proposed a new saprophytic clade, S2, that is branched from the saprophytic clade S1 which is composed of previously known saprophytic Leptospira species, such as L. biflexa and L. meyeri . These five isolates, as well as E30, E107, E101, E154, E156, L. ryugenii strain YH101, and L. idonii strain Eri‐1 isolated from water were found to belong to the S2 clade. Furthermore, it was revealed that some Leptospira species showed identical rrs sequences, because this leptospiral gene is highly conserved among Leptospira species .…”
Section: Culture‐positivity Rate Of Leptospira In Environmental Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Leptospirosis is caused by an infection with spirochete bacterium of the genus Leptospira and affects humans as well as a broad spectrum of animal hosts. There are currently 27 Leptospira species as delineated by DNA–DNA hybridization ( Masuzawa et al., 2019 ). Phylogenetic analysis of these species using the 16S rRNA gene has resulted in the broad classification of the species into pathogenic, saprophytic and intermediate ( Perolat et al., 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is caused by the pathogenic species of Leptospira, primarily Leptospira interrogans . Till date, 38 species of Leptospira have been identified: 13 pathogenic, 12 intermediates, and 13 non-pathogenic (saprophytes) [5,6]. L. interrogans persistently colonizes the proximal renal tubules of carrier animals, and, once infected, the carrier animals remain symptom-free and shed infectious organisms in urine for their entire lifetime [7].…”
Section: Introductionmentioning
confidence: 99%